Migration rate using fully covered metal stent in anastomotic strictures after liver transplantation: Results from the BASALT study group. (12th April 2022) - Conigliaro, Rita; Pigò, Flavia; Bertani, Helga; Greco, Salvatore; Burti, Cesare; Indriolo, Amedeo; Di Sario, Antonio; Ortolani, Alessio; Maroni, Luca; Tringali, Andrea; Barbaro, Federico; et al.
Abstract: Background and Study Aim: The traditional endoscopic therapy of anastomotic strictures (AS) after orthotopic liver transplantation (OLT) is multiple ERCPs with the insertion of an increasing number of plastic stents side‐by‐side. Fully covered self‐expanding metal stents (cSEMS) could be a valuable option to decrease the number of procedures needed or non‐responders to plastic stents. This study aims to retrospectively analyse the results of AS endoscopic treatment by cSEMS and to identify any factors associated with its success. Patients and Methods: Ninety‐one patients (mean age 55.9 ± 7.6 SD; 73 males) from nine Italian transplantation centres, had a cSEMS positioned for post‐OLT‐AS between 2007 and 2017. Forty‐nine (54%) patients were treated with cSEMS as a second‐line treatment. Results: All the procedures were successfully performed without immediate complications. After ERCP, adverse events occurred in 11% of cases (2 moderate pancreatitis and 8 cholangitis). In 49 patients (54%), cSEMSs migrated. After cSEMS removal, 46 patients (51%) needed further endoscopic (45 patients) or radiological (1 patient) treatments to solve the AS. Lastly, seven patients underwent surgery. Multivariable stepwise logistic regression showed that cSEMS migration was the only factor associated with further treatments (OR 2.6, 95% CI 1.0–6.6; p value 0.03); cSEMS implantation before 12 months from OLT was associated with stent migration (OR 5.2, 95% CI 1.7–16.0; p value 0.004). Conclusions: cSEMS appears to be a safe tool to treat AS. cSEMS migration is the main limitation to its routinary implantation and needs to be prevented, probably with the use of new generation anti‐migration stents.